Evaluation of serum ferritin level and hepatitis b and hepatitis c viral infection in chronic hemodialysis patients: Serum ferritin and hepatitis B and C in HD - R. Shawgery, Hemn (Cellular and Molecular Biology, 2024)
The most popular treatment for end-stage renal illness is hemodialysis (HD). The study aimed to assess serum ferritin levels and their connection to Epoetin alfa resistance, along with exploring the link between hepatitis C virus, iron overload, and the prevalence of hepatitis C and B infections in chronic HD patients. This was a descriptive-analytical study conducted on 50 Patients with chronic kidney disease (CKD) who were on regular HD in the dialysis unit of Ibin Sina Teaching Hospital in Mosul City, Iraq. Out of 50 patients, 26 (52%) tested positive for Hepatitis C Virus (HCV) Antibody, 10 (20%) for Hepatitis B surface Antigen (HBsAg), and 14 (28%) tested negative for both. Higher serum iron and ferritin levels were found in HCV antibody-positive patients (p < 0.05). Despite Epoetin alfa treatment, patients with elevated ferritin levels exhibited lower Hemoglobin (HB) and Packed Cell Volume (p < 0.05). Non-diabetics exhibited significantly higher serum ferritin, Hemoglobin, Blood urea, and serum creatinine than diabetics (p < 0.05). A noteworthy association was seen between the quantity of blood transfusions and elevated levels of serum ferritin and total serum iron (p < 0.05). Most HD patients were anemic, with Hepatitis B and C prevalent. The main CKD causes were diabetes and hypertension. HCV-positive patients often showed mild to moderate iron overload, and high serum ferritin was linked to poor Epoetin alfa response. Dialysis can elevate blood urea, ferritin, and creatinine, worsening anemia. High ferritin levels may hinder response to Epoetin alfa and iron replacement. Excessive blood transfusions can lead to iron overload and inhibit erythropoiesis. Maintaining HB at 110-120 g/l improves quality of life and reduces anemia-related risks.